Oral Health and Dental Students' Perceptions of Their Clinical Learning Environment: A Focus Group Study. Issue 10 (1st October 2018) - Ebbeling, Sarah; Adam, Lee; Meldrum, Alison; Rich, Alison; McLean, Angela; Aitken, Wendy
Abstract : Creating an optimal clinical learning environment poses a challenge to health professions educators. To evaluate and improve the clinical learning environment, it is necessary to understand students' experiences of their environment and the factors they perceive as having an impact on their learning. The aim of this explorative qualitative study was to examine University of Otago Faculty of Dentistry students' perceptions of their clinical learning environment to gain insights into how learning outcomes could be enhanced. In 2015, all approximately 600 students at all levels of the Bachelor of Oral Health and Bachelor of Dental Surgery degrees at the University of Otago, Dunedin, New Zealand, were invited to participate in focus groups. Focus groups facilitated by the faculty education research fellow and another researcher employed for the project were conducted during the second half of the academic year. Transcribed data were analyzed using a general inductive approach. Twenty‐one students from all levels of the two programs attended one of six confidential focus groups. Three broad themes were evident in the results from all groups: feedback processes, assessments and grading, and tutor interactions. In the focus groups, students expressed dissatisfaction regarding current feedback practices, types of feedback to benefit learning, consistency in the grading system, and impact of different educators' teaching styles on learning. These results indicated a need for further research and curricular efforts to promote good student‐teacher relationships in the clinical learning environment, which are paramount for creating an optimal teaching and learning environment and enhancing student outcomes.